IMAGERY IN JULIANNE MACLEAN’S THE COLOR OF HEAVEN - Lestysiana Dwi Sevtira; Yoseph Bavo Agung Prasaja (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
Imagery is a mental picture imagined by a reader. This research discusses imagery that existed in Julianne MacLean's novel The Color of Heaven. The Color of Heaven is a novel that tells about Sophie Duncan's life and there is a lot of imagery used in it. The objectives of this research are to find imageries in the novel, to identify and classify the types of imagery, and to reveal the purposes of the imagery. The researcher uses Laurence Perrine's theory through Johnson & Arp (2016) about seven types of imagery which are visual imagery, auditory imagery, olfactory imagery, tactile imagery, organic imagery, and kinesthetic imagery. The researcher uses qualitative research design since the analysis explains the types and the purpose of the imagery. The study uses a formalism approach because the analysis is based on the researcher's interpretation. The data are collected straight from the book by reading it several times and taking notes of the sentence that reflects imagery, then categorizing the data into its imagery types in the form of a list. The result of the analysis shows that there are found six types of imagery except one is gustatory imagery. There are 32 visual imagery, 34 auditory imagery, 12 olfactory imagery, 11 tactile imagery, 16 organic imagery, and 20 kinesthetic imagery found in the novel.